2016
DOI: 10.1097/prs.0000000000002108
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Corneal Abrasion: Updated Guidelines for Prevention and Management

Abstract: Corneal abrasion is the most common ocular complication in surgery. Treatment requires pain control, antimicrobial prophylaxis, and close monitoring. Pain improves significantly after 24 hours and should be resolved by 48 hours. Persistent, worsening, or new symptoms warrant immediate specialist consultation. The authors review the pathophysiology of perioperative corneal abrasion, and propose updated evidence-based guidelines for improved patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 73 publications
0
23
0
Order By: Relevance
“…These complications are often observed in humans during and after surgery, leading to manifestation of iatrogenic corneal lesions or so-called perioperative DES. Yet, the exposure of rabbits to general anesthesia resulted in the development of the majority of symptoms characteristic of common age-related DES, which makes such a model appropriate for testing general approaches to treatment of this disorder [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These complications are often observed in humans during and after surgery, leading to manifestation of iatrogenic corneal lesions or so-called perioperative DES. Yet, the exposure of rabbits to general anesthesia resulted in the development of the majority of symptoms characteristic of common age-related DES, which makes such a model appropriate for testing general approaches to treatment of this disorder [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ageing, prolonged eye strain, environmental factors, medication intake, and refractive surgery are the major contributors to DES development [ 4 ]. General anesthesia is another risk factor for DES, which is becoming more prominent with wider use of surgical interventions in modern medicine [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DES affects up to 40% of the adult population and manifests as eye irritation, hyperemia, glare, eye fatigue, and blurred vision [2,3]. Etiologically, alterations in tear homeostasis are associated with dysfunction of the lachrymal and/or Meibomian glands (such as in Sjögren syndrome and Meibomian Gland Dysfunction (MGD)) as well as a number of other factors, including contact lens wearing, adverse effects of various medications, complications of ocular surgery and general anesthesia [1,[4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we developed a rabbit model of DES, closely reproducing the pathogenesis of the human disease [27]. In this model, DES is induced by exposure of the animals to general anesthesia, which diminishes the production of basal and reflex tears and decreases the stability of the tear film thereby inducing common signs of the disease [4,28]. In a more recent study, we adopted a quantitative UPLC-MS/MS-based approach to identify and characterize baseline patterns of lipid mediators in the TF of healthy rabbits and demonstrated that they did not differ significantly from that of human TF [29].…”
Section: Introductionmentioning
confidence: 99%